Cloud Disruption Impacts Business IT Role Requirements. Issue 5 (3rd September 2022) - Cusack, Brian; Adedokun, Adekemi
ABSTRACT: Cloud computing (Cloud) introduces new information technology (IT) optimization challenges for business management. The traditional supply of IT services is disrupted by more diverse and cost-efficient options where all IT services can be rented or leased on-demand to suit a business requirement. The implication is for a forecasted discontinuation of many IT workplace roles and the formulation of others to fit the new requirements. This exploratory research shows that the IT service supply chain has been disrupted and that Cloud is a driver for business structural change. We asked: What are the impacts of cloud computing on business information system (BIS) IT services roles? A targeted sample of industry Cloud professionals were consulted, and the data thematically analyzed. The data analysis showed seven general business impact categories and six classes for BIS IT role impacts. These findings contribute understanding of uncertainty around the new business IT role requirements.